1968
DOI: 10.1139/z68-015
|View full text |Cite
|
Sign up to set email alerts
|

Ecological significance of respiration and substrate for burrowing Ephemeroptera

Abstract: In an attempt to understand the differential distribution of Ephemera simulans and Hexagenia limbata in intergrading substrates, the author extended his studies of the ecological roles of the laboratory-derived comparisons of respiration, morphology, and behavior.Conclusions drawn, mainly from my earlier and present work and also work reported by Lyman in 1943 and Hunt in 1953, seem to be consistent with field distribution. It appears that H. limbata is not found in streams unless prevailing conditions include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…They consume algae and plant debris, deriving nutrients from organic material in the sediment along with digesting some bacteria (Hunt 1953). The character of the bottom sediment is the most essential factor in describing the abundance and distribution of mayfly nymphs (Lyman 1943;Hunt 1953;Ericksen 1968;Wright and Mattice 1981). However, many other factors come into play including dissolved oxygen levels, predation, sedimentation, water temperature, sediment contamination, and flow (Hunt 1953;Mauck and Olson 1977;Clements and Kawatski 1984;Rasmussen 1988;Koel and Stevenson 2002).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…They consume algae and plant debris, deriving nutrients from organic material in the sediment along with digesting some bacteria (Hunt 1953). The character of the bottom sediment is the most essential factor in describing the abundance and distribution of mayfly nymphs (Lyman 1943;Hunt 1953;Ericksen 1968;Wright and Mattice 1981). However, many other factors come into play including dissolved oxygen levels, predation, sedimentation, water temperature, sediment contamination, and flow (Hunt 1953;Mauck and Olson 1977;Clements and Kawatski 1984;Rasmussen 1988;Koel and Stevenson 2002).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Eriksen (1964) showed that the burrowing mayfly Ephemera simulans (Ephemeridae) usually selected fine gravel for burrowing in laboratory tests. He also showed that although the mayfly could burrow in a variety of substrate sizes, the relatively low DO of finer sediments in field situations limited the mayfly to substrates with larger interstices (Eriksen, 1968). McCafferty (1975) first discovered young larvae of Anthopotamus within substrate (at approximately 0.5 m depth) while searching for burrowing mayflies of the genus Ephoron on the Tippecanoe River.…”
Section: Discussionmentioning
confidence: 99%
“…protection against predation and disturbance, and acquisition of food and oxygen (e.g. Eriksen, 1968). It is therefore of critical importance for both species to find a substrate in which they can construct a stable tube.…”
Section: Substrate Typementioning
confidence: 99%
“…Therefore many benthic invertebrates enhance oxygen uptake by creating currents across boundary layers by ventilatory movements. Burrowing mayfly nymphs beat their gills with a frequency inversely related to the oxygen concentration in their burrow, to maintain a current through their burrow which directly functions in oxygen uptake (Eriksen, 1968). Van der Geest et al (2001) demonstrated that anoxic and hypoxic conditions had detrimental effects on the survival of early E. virgo nymphs, but at oxygen concentrations of 50% or higher, no effects on survival were observed after 4 days of exposure.…”
Section: Oxygenmentioning
confidence: 99%